Unearthly Nature: The Strangeness of Arbospaces in Thomas Hardy’s The Woodlanders - Pigoń, Zofia (Text Matters: A Journal of Literature, Theory and Culture, 2024)
Commonly acknowledged as one of Thomas Hardy’s most environmentally-conscious literary accomplishments, The Woodlanders (1887) provides fertile ground for a stimulating and topical ecocritical debate. The intricate correlation between the natural and the human—indicated by the very title—undergirds the structure of the text and creates unique narrative collisions while simultaneously propelling the development of the plot. The multiple references to the sphere of the paranormal—realized in the passages pertaining to local lore and, most significantly, in the descriptions of the setting—reflect the conflation of superstition and uncanniness, which adds otherworldly overtones to the novel. The article analyzes these qualities insofar as they shape the portrayed landscape—specifically, the woodscape—as a realm whose essence continually balances between the fantastical and the real. It also examines how the natural and human elements are reciprocally subsumed by means of anthropomorphic language and how this occurrence can be interpreted through the lens of intertextuality. By focusing on these rather antithetical concepts, I wish to demonstrate how the boundaries between them are elided, thus preserving an aura of ambivalence that pervades the novel.